Entropy and Organizational Performance - Neves, José (2019)
The main purpose of this article is to analyze the impact of the workers’ behavior in terms of their emotions and feelings in system’s performance, i.e., one is looking at issues concerned with Organizational Sustainability. Indeed, one’s aim is to define a process that motivates and inspires managers and personnel to act upon the limit, i.e., to achieve the organizational goals through an effective and efficient implementation of operational and behavioral strategies. The focus will be on the importance of specific psychosocial variables that may affect collective pro-organizational attitudes. Data that is increasing exponentially, and somehow being out of control, i.e., the question is to know the correct value of the information that may be behind these numbers.